2006
DOI: 10.12968/denu.2006.33.4.242
|View full text |Cite
|
Sign up to set email alerts
|

Does Low Acid Orange Juice Equal Low Erosion?

Abstract: As dietary advice forms a cornerstone in the clinical management of erosion, the introduction of a commercially available low acid orange is most welcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
1
5
0
5
Order By: Relevance
“…This was close to previous findings 5.27 μm, 35 3.23 μm, 36 5.2 μm, 37 and 5.3 μm. 21 The results of this study also showed that there was no significant effect of saliva on the amount of surface enamel loss (p >0.05), but it did significantly reduce the subsurface enamel loss (p <0.05).…”
Section: Discussionsupporting
confidence: 92%
“…This was close to previous findings 5.27 μm, 35 3.23 μm, 36 5.2 μm, 37 and 5.3 μm. 21 The results of this study also showed that there was no significant effect of saliva on the amount of surface enamel loss (p >0.05), but it did significantly reduce the subsurface enamel loss (p <0.05).…”
Section: Discussionsupporting
confidence: 92%
“…In vitro studies have shown that fruit juices may also be potentially erosive because of their high content of titratable acid (Jensdottir et al,2005; Larsen and Nyvad,1999; Lussi et al,1995). Orange juice contains high levels of citric acid that chelates calcium, and this effect is thought to increase the erosive capability (Rees et al,2006). Despite these characteristics, the orange juice used in the present study was less erosive than gastric juice.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] In the present study, however, 100 ml of drink was used due to the thickness of both the fruit smoothies and the yoghurt 'thickie' investigated. On a practical basis such a volume promoted the efficient mixing of drink and chemical reagents.…”
Section: Baseline Ph and Titratable Acidity (Sta)mentioning
confidence: 99%
“…In contrast, other beverage studies only used 20 ml of drink, perhaps due to the lower viscosities of the drinks under investigation. 21 In the present work a non-heating magnetic stirrer, set at the highest stirring rate, was used to provide sufficient momentum to permit mixing due to the drinks' thick consistencies. As Shellis et al found, stirring rate influences both the rate of erosion and rate of dissolution of tooth substance so this was kept constant in the work reported here.…”
Section: Baseline Ph and Titratable Acidity (Sta)mentioning
confidence: 99%
See 1 more Smart Citation